Agents of S.U.I.T. : from badger to worse - Green, John Patrick, 1975-; Hastings, Chris, 1983- (Green, John Patrick, 1975- InvestiGators (Series), 2024)
"In the first book of Agents of S.U.I.T., the new volume in John Patrick Green's smash-hit InvestiGators world, eager rookie agent Cilantro stepped into the spotlight and rocketed into space! Now it's time for the B-Team to show why they're so un-B-lievably B-loved. That's right, Bongo and Marsha, the superspy Badgers, are on the case . . . and way over-budget. When S.U.I.T. realizes just how much money the Badgers waste with their gadgets and spy vehicles and custom plush toys, they're sent to Bora Bora to investigate a case...the old-fashioned way. The bees that's bee-ee-ee, like the insect that run the resort are hiding something under the tropical sands, and Marsha and Bongo are just the bumbling agents to crack this pineapple-flavored case wide open."--Provided by publisher.